Are the clinical benefits of oral prenalterol in ischaemic heart failure due to beta blockade? A six month randomised double blind comparison with placebo. Issue 2 (February 1985) - Glover, D R; Wathen, C G; Murray, R G; Petch, M C; Muir, A L; Littler, W A
Abstract : The clinical effects of the oral beta 1 partial agonist, prenalterol, were investigated in 37 patients (29 male, eight female; mean age 57 years) with chronic ischaemic left ventricular failure using a placebo controlled randomised double blind protocol over six months. All patients were limited by dyspnoea (New York Heart Association class III) despite treatment with digoxin and diuretics. Twenty eight patients completed the protocol. Moderate clinical improvement was seen in the prenalterol group, whereas there was little change in the placebo group. Bicycle exercise capacity increased over six months in the prenalterol and placebo groups but only achieved statistical significance for prenalterol when compared with baseline values. Maximum exercise heart rate was significantly reduced in the prenalterol group compared with placebo. Radionuclide left ventricular ejection fraction at rest and during exercise and cardiothoracic ratio showed no significant improvement in either group over six months. Prenalterol was well tolerated and produced no increase in frequency of angina or ventricular arrhythmias. Prenalterol produced clinical benefits and improved exercise tolerance while reducing exercise heart rate. A moderate placebo response was noted. The apparent beta blocking effect of prenalterol may be as important as the beta 1 agonist effect in producing these benefits. Prenalterol has, however, been withdrawn because of side effects in animals.